1989
DOI: 10.1165/ajrcmb/1.2.145
|View full text |Cite
|
Sign up to set email alerts
|

Alveolar Macrophage-Particle Relationships during Lung Clearance

Abstract: Retention kinetics for insoluble particles that deposit in the lung oftentimes resemble a multicomponent process during alveolar clearance, with each component appearing to follow simple first-order kinetics. Inasmuch as alveolar macrophages (AM) are thought to play an important role in particle removal from the lung, a study was undertaken to examine particle-AM relationships during the clearance of particles to obtain information on potential AM mechanisms that could provide the underlying bases for the lung… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
38
6

Year Published

1992
1992
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(48 citation statements)
references
References 25 publications
3
38
6
Order By: Relevance
“…Otherwise, the process ofphagocytosis, i.e., particle encounters and engulfment by AM, seemingly would have to be accomplished with complete efficiency within a post-depositional time span that would preclude particle uptake by the type I cells. The above extension ofthe Adamson and Bowden postulate is consistent with numerous reports that particles appear in the regional lymph nodes even when they are deposited at relatively low lung burdens (105,106,118,132). Assuming particle phagocytosis by AM is not perfectly efficient and sufficiently rapid, increasing numbers of particles would be expected to gain entry into type I cells essentially continuously during chronic aerosol exposures even ifthe phagocytic capacities of alveolar phagocytes have not been ex- FIGURE 15.…”
Section: Pulmonary Interstitial Macrophagessupporting
confidence: 84%
See 3 more Smart Citations
“…Otherwise, the process ofphagocytosis, i.e., particle encounters and engulfment by AM, seemingly would have to be accomplished with complete efficiency within a post-depositional time span that would preclude particle uptake by the type I cells. The above extension ofthe Adamson and Bowden postulate is consistent with numerous reports that particles appear in the regional lymph nodes even when they are deposited at relatively low lung burdens (105,106,118,132). Assuming particle phagocytosis by AM is not perfectly efficient and sufficiently rapid, increasing numbers of particles would be expected to gain entry into type I cells essentially continuously during chronic aerosol exposures even ifthe phagocytic capacities of alveolar phagocytes have not been ex- FIGURE 15.…”
Section: Pulmonary Interstitial Macrophagessupporting
confidence: 84%
“…Moreover, the conclusions drawn in these studies would have gained further support ifcomparisons ofthe frequency distributions ofparticles in the lung free-cells and lung lymph nodes had been shown to be similar. Nevertheless, the above studies collectively seem to suggest that particle-containing AM may indeed make their way as one approach to obtain information on potential AM-related mechanisms that could form the underlying bases for conventional depictions of alveolar clearance (132). Briefly, the apparent overall rate(s) ofdisappearance of AM from the total AM population over time was found to increase with increasing particle burdens contained in the AM (Fig.…”
Section: Pulmonary Macrophages Alveolar Macrophagesmentioning
confidence: 94%
See 2 more Smart Citations
“…Exhaustive total bronchalveolar lavages (BAL) in rodents up to half a year after particle administration (38,39) showed that more than 80% of the retained particles were still retained in AM on the epithelium. In large animals, partial BAL suggested particle retention in AM up to 500 days after inhalation (14,31,40,41).…”
Section: Particle Phagocytosis and Retentionmentioning
confidence: 99%